Penerapan Metode Al-Miftah Dalam Meningkatkan Pemahaman Kaidah Nahwu di Madrasah Tsanawiyah Mambaus Sholihin Gresik - Makinuddin, Mohammad; Friendis Syani Amrulloh (Universitas KH. Mukhtar Syafaat, 2026)
The implementation of the Al-Miftah Method in Nahwu learning at Madrasah Tsanawiyah Mambaus Sholihin Gresik aims to improve students' understanding of Nahwu rules functionally, addressing the weaknesses of traditional methods that focus more on memorization. This study employs a case study design with a qualitative approach, collecting data through observation, interviews, and documentation. The results show that the Al-Miftah Method can enhance students' understanding in a gradual and contextual manner by relating Nahwu theory directly to real sentence examples. The inductive approach applied in this method successfully integrates theory and practice, strengthening students' functional understanding of Nahwu rules. An increase in active participation and learning motivation was also observed, which contributed to the improvement of students' Arabic language skills. These findings indicate that the Al-Miftah Method is an innovative solution to improve the effectiveness of Nahwu learning at the Madrasah Tsanawiyah level, which can be applied in pesantren and similar educational institutions to strengthen the functional and meaningful understanding of Arabic.